2022
DOI: 10.1001/jamanetworkopen.2022.5982
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Cost-effectiveness of an Empowerment-Based Self-care Education Program on Health Outcomes Among Patients With Heart Failure

Abstract: IMPORTANCEStrategies that enhance self-care of patients with heart failure reduce mortality and health care use. OBJECTIVE To examine whether an empowerment-based self-care education program was more effective and cost-effective to improve self-care, health status, and hospital service use than a didactic education program in patients with heart failure. DESIGN, SETTING, AND PARTICIPANTS In this double-blind randomized clinical trial, a consecutive sample of 988 patients with heart failure from the cardiac cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 46 publications
0
58
1
Order By: Relevance
“…Effective symptom recognition and appropriate response (such as self-care management) have appeared crucial to prevent disease related events and delayed care seeking. 22,23 We advocate to implement these same strategies for nocturia, although we are aware that the medical burden of nocturia cannot be compared to that of diabetes or chronic heart failure. This discrepancy might lower the incentive of health care professionals to invest in the education, therapy and follow up for a condition that some might see as a normal age-related phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective symptom recognition and appropriate response (such as self-care management) have appeared crucial to prevent disease related events and delayed care seeking. 22,23 We advocate to implement these same strategies for nocturia, although we are aware that the medical burden of nocturia cannot be compared to that of diabetes or chronic heart failure. This discrepancy might lower the incentive of health care professionals to invest in the education, therapy and follow up for a condition that some might see as a normal age-related phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from chronic disease such as diabetes mellitus and chronic heart failure have been encouraged, educated and given the tools to successfully cope with their condition. Effective symptom recognition and appropriate response (such as self‐care management) have appeared crucial to prevent disease related events and delayed care seeking 22,23 . We advocate to implement these same strategies for nocturia, although we are aware that the medical burden of nocturia cannot be compared to that of diabetes or chronic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Such side effects are usually temporal, that is, the most severe 3–7 days after each cycle. During the 3-month intervention period, patients received four chemotherapy treatment cycles, which were sufficient to assess the effects of the intervention [ 30 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ni et al [ 29 ] showed that empowerment education improved caregiving knowledge, caring behaviors, and self-efficacy among parents caring for children with congenital heart disease. Yu et al [ 30 ] identified the significant effects of a group-based empowerment educational program on improving symptom perception, self-care management, and QoL in patients with heart failure. Schmidt et al [ 31 ] indicated that empowerment education through informational booklets and diary keeping improved the perioperative quality of care in elderly onco-surgical patients.…”
Section: Introductionmentioning
confidence: 99%
“…While self-care is broader and involves all activities such as preventive measures and includes disease management activities (Grady & Gough, 2014), self-health management is often used for disease/symptom management and was used predominantly in clinical settings and theory development (Ryan & Sawin, 2009). However, recent literature shows self-care being used in clinical settings as well (Yu et al, 2022). In this paper, we use the term self-care for the broader CDSSS and self-health management for disease/symptom tracking.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%